Evaluación de fuentes fosfóricas sobre el rendimiento del cultivo de arroz (Oryza sativa L.) bajo riego en la zona de Babahoyo - Minda López, Walter Clemente (2017)
VIII. SUMMARY The experimental work was carried out in the lands of the experimental farm of the Ability of Agricultural Sciences of the Technical University of Babahoyo in the sector Palmar, located in Km 11,5 of the road Babahoyo-Montalvo. Six treatments and four repetitions were investigated. The objective of this investigation was to evaluate the agronomic behavior of of the rice with the application of phosphoric sources, to find the most influential product on the production of the cultivation. The crop of rice was made with the varieties SFL-11 in parcels of 24 m2. The treatments were distributed at random in a design of complete blocks. For the evaluation of stockings the test was used from Tukey to 5 % significance. The evaluated variables were: height of plants, plants number for m2, grains for panicule, longitude and number of panicule m2, days to flowering, days to crop, number of grains for panicule, weight 1000 seeds, yield for hectare, agronomic efficiency, analysis to foliate and economic analysis. The results determined that the agronomic characteristics of plant height, plants number, panicules/m2, panicule longitude, grains for panicule, days to flowering and days to crop they didn't present statistical significance. The biggest yield in the cultivation (6405,61 kg/ha) it was presented applying ammonium Di-phosphate DAP-AVAIL 114 kg/ha in the variety SFL-11, the same one that also present bigger agronomic efficiency (25,98 %). The Witness presented the lowest averages in the studied variability. Keywords: rice, fertilization, production, soils, sources.